Super Activated Platelet Lysate, a Novel Autologous Platelet Lysate, Regulates the Expression of Inflammasome and Cytokine in the Experimental Periodontitis in Rats - Zhang Y; Zhuang D; Zhang Y; Lu H; Zhang H; Li T; Bi L (Dove Medical Press, 2020)
Yi Zhang,1 Deshu Zhuang,1,2 Yi Zhang,3 Huiying Lu,3 Haijiao Zhang,3 Tingting Li,3 Liangjia Bi1 1Department of Stomatology, The Fourth Affiliated Hospital, Harbin Medical University, Harbin 150001, People’s Republic of China; 2Faculty of Dentistry, Department of Oral Biological and Medical Sciences, University of British Columbia, Vancouver BC V6T 1Z3, Canada; 3National and Local Joint Stem Cell Research & Engineering Center for Aging Diseases, Tian Qing Stem Cell Co., Ltd., Harbin 150028, People’s Republic of ChinaCorrespondence: Liangjia BiDepartment of Stomatology, The Fourth Affiliated Hospital, Harbin Medical University, Harbin 150001, People’s Republic of ChinaTel/Fax +86-451-82576565Email biliangjia6601@126.comPurpose: The aim of the present study was to evaluate the expression of inflammasome and cytokine on experimental periodontitis with super activated platelet lysate (SPL) in rats.Methods: Periodontitis was induced by submerging cotton ligatures on the right side of the maxillary second molar in 36 Wistar rats. The rats were divided into 3 groups randomly: the rats received no treatment (control group); local injection with sterile saline (ligature+saline group) and local injection with SPL (ligature+SPL group). After treatments, the alveolar bone level and inflammation of periodontal tissue were evaluated by micro-computed tomography (micro-CT) scanning and histological examination, respectively. The expression of inflammasome and cytokine was evaluated by real-time quantitative polymerase chain reaction (RT-qPCR) assay.Results: Compared with the control group, the bone loss significantly increased by 0.9 mm in the ligature+saline group and 0.4 mm in the ligature+SPL group (P < 0.001). 0.5 mm reduction in the bone loss was founded in the ligature+SPL group compared with the ligature+saline group (P < 0.001). The gene expression of CCL2, CXCL2, IL-6, IL-18, IL-1α, IL-1β, CXCL10, CXCL16, CCL5 was significantly reduced in the ligature+SPL group compared with the ligature+saline group (P < 0.05). Compared with the ligature+saline group, the expression for inflammasome NLRP3, AIM2, CASP1 was both downregulated in the ligature+SPL group (P < 0.05).Conclusion: Our present study demonstrated local injection of SPL regulated the expression of inflammasome and cytokine and had a visible effect of relieving inflammation in the experimental periodontitis in rats.Keywords: periodontitis, super activated platelet lysate, inflammasome, cytokine